Therapeutic Horseback Riding Crossover Effects of Attachment Behaviors with Family Pets in a Sample of Children with Autism Spectrum Disorder - Petty, Jessie D. (Int J Environ Res Public Health, 2017)
The unique needs of individuals with autism spectrum disorder (ASD) have implications for animal welfare. This nested pilot study examined the effects of a randomized trial of 10-week therapeutic horseback riding (THR) intervention versus a no-horse barn activity (BA) control group on children’s behaviors with family pets. Sixty-seven (THR n = 31; BA n = 36) participants with ASD (ages 6–16 years) with one or more family pet, were enrolled from a larger trial (n = 116) following their randomization to intervention groups, stratified by nonverbal intellectual ability. A consistent caregiver completed questionnaires about participants’ interactions with their household pets pre- and post-intervention. Caregivers of THR group participants reported significant improvements in participants’ caring actions with the family pet compared with the BA group (p = 0.013; effect size = 0.74). Engaging with horses during a standard THR intervention protocol may generalize to improving caring actions toward family pets in children and adolescents with ASD.